Optimization of cellulase enzyme immobilization onto magnetic nickel nanoparticles using a 24 full factorial design - Sasi, Ahmed; Mustafa, Abu Hasnat; Sikder, Md. Belal Hossain; Jaya Vejayan, Palliah; Rashid, Shah Samiur; Mohd Hasbi, Ab Rahim (AIP Publishing, 2025)
Cellulase immobilization is an important issue for cellulose hydrolysis in biochemical applications. The focus of this work is the optimization of the process of cellulase enzyme immobilization on synthetic nickel nanoparticles (NiNPs) used as a support. To determine the effects of four parameters on the optimization of cellulase activity, a 24-full factorial design was used in this study. Since magnetic NiNPs significantly improve catalyst reutilization and eliminate the need for time and energy-intensive centrifugation processes, they can be thought of as supports for enzyme immobilization. Indeed, the high cost of enzymes means that techniques for enzyme immobilization that offer high biocatalyst stability are highly desired. Important enzymes can be immobilized at the industrial level using NiNPs because they have improved enzymatic application properties with facile and quick recovery for reutilization. The ideal conditions for the optimization process were found to be time = 3 hours, enzyme concentration = 3 mg/mL, temperature = 40 °C, and pH = 4. The remaining productivity after reutilization of the immobilized enzyme was found to be greater than 50% after 5 rounds of recycling. Since this type of immobilized cellulase may be easily recovered from the reaction solution, enzyme reutilization can be easily achieved.